Analisis Motivasi Kerja terhadap Produktifitas Kerja Karyawan pada Usaha Krupuk Uenak Bu Rina - Regita Diaz Pramesti; Lintang ArindaSanti; Yudi Ali Wardana (Jurnal Transformasi Bisnis Digital, 2026)
This study aims to analyze the influence of work motivation on employee productivity at Kerupuk Uenak Bu Rina, a home-based industry in Boyolali. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews and direct observation at the business location. The results indicate that work motivation derived from internal factors such as satisfaction with received wages and a familial work environment, as well as external factors in the form of appreciation from the owner, significantly influence employee morale and work output. Employee productivity levels are reflected in the consistency in meeting production targets for two types of crackers and the ability to adapt to demand fluctuations. These findings suggest that improving productivity in micro-enterprises like this one depends not only on technical operational aspects but is also greatly influenced by how work motivation is managed. This research provides practical contributions regarding the importance of paying attention to human resource aspects in managing operational risks and improving the performance of small-scale businesses.